2020
DOI: 10.3390/math8060955
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for Production Plan Optimization—A Case Study of Discrete Event Systems

Abstract: This paper proposes an optimal scheduling model under production and maintenance constraints for a real case of a discrete event system. The intent was to use the rich mathematical theory and algorithms of optimization in the study of this important class of systems. The current study detailed firstly a new approach for mapping a simulation event relationship graph into a mixed-integer program, with a flexible workshop real case. Several other potential applications of the mathematical model are examined, than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The Petri net supervisor in our methodology can be defined by a set of control places ∑ P c . The control place P c can be calculated by solving the linear system of the theory of regions [18][19][20][21][22]. This linear system is composed of three types of conditions.…”
Section: Tools and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Petri net supervisor in our methodology can be defined by a set of control places ∑ P c . The control place P c can be calculated by solving the linear system of the theory of regions [18][19][20][21][22]. This linear system is composed of three types of conditions.…”
Section: Tools and Methodsmentioning
confidence: 99%
“…State number 7 is a blocking state [21] and will lead to a deadlock. So, it is considered a forbidden state.…”
Section: Tools and Methodsmentioning
confidence: 99%
“…As regards the worker performing moulding operation causes would be Anthropometric Information about the operator -dimension from foot fingers to knee, from knee to waist, waist to chest, knee to chest, from shoulder to elbow, elbow to fingers etc [9].Tools for the operation -Weight of Pattern, Ram, and Moulding box .Responses (i.e. effects) (Output) would be Productivity (Opt1), Human Energy input (Opt2).…”
Section: Identification Of System Constants and Process Parametersmentioning
confidence: 99%
“…Furthermore, a GA is proposed to find efficient solutions for big scheduling problems. (Rezig et al 2020) develops a scheduling model with production and maintenance constraints for a discrete event system based on Petri nets. The study demonstrated the performance of the mathematical model, an implementation example of the approach such as hospital bed management.…”
Section: Introductionmentioning
confidence: 99%